PENGARUH INTERVENSI KELOMPOK DUKUNGAN SEBAYA TERHADAP MEKANISME PENYESUAIAN DIRI PADA WANITA DENGAN SINDROM PRAMENSTRUASI - Rintan Rikawati; Henny Dwi Susanti (Jurnal Medicare, 2026)
Background: Premenstrual Syndrome (PMS) is a reproductive health disorder characterized by physical, emotional, and behavioral symptoms during the luteal phase of the menstrual cycle, which can interfere with daily activities, academic performance, social relationships, and quality of life. Methods: This study used a case report design involving a 19-year-old female adolescent who experienced dysmenorrhea, mood swings, and decreased concentration. Coping mechanisms were assessed using the Premenstrual Change Coping Inventory (PMS-COPE) before and after the intervention. The Junk foodintervention included education about PMS, sharing experiences, group discussions, emotional support, reflection, and practice of adaptive coping strategies. Results: The PMS-COPE score increased from 53 to 54 after the intervention. In addition, the patient became better able to recognize PMS symptoms, was more open to sharing experiences, felt more confident in dealing with emotional changes, began to utilize peer support, and applied more adaptive coping strategies. Conclusion: The Junk foodhas the potential to improve coping mechanisms in adolescent girls with PMS and can be considered as a nonpharmacological nursing intervention to support adaptation to PMS symptoms.